Hyperpolarization of Pyridyl Fentalogues by Signal Amplification By Reversible Exchange (SABRE). Issue 12 (8th November 2019) - Robertson, Thomas B. R.; Antonides, Lysbeth H.; Gilbert, Nicolas; Benjamin, Sophie L.; Langley, Stuart K.; Munro, Lindsey J.; Sutcliffe, Oliver B.; Mewis, Ryan E.
Abstract: Fentanyl, also known as 'jackpot', is a synthetic opiate that is 50–100 times more potent than morphine. Clandestine laboratories produce analogues of fentanyl, known as fentalogues to circumvent legislation regarding its production. Three pyridyl fentalogues were synthesized and then hyperpolarized by signal amplification by reversible exchange (SABRE) to appraise the forensic potential of the technique. A maximum enhancement of ‐168‐fold at 1.4 T was recorded for the ortho pyridyl 1 H nuclei. Studies of the activation parameters for the three fentalogues revealed that the ratio of ligand loss trans to hydride and hydride loss in the complex [Ir(IMes)(L)3 (H)2 ] + (IMes=1, 3‐ bis (2, 4, 6‐trimethylphenyl)imidazole‐2‐ylidene) ranged from 0.52 to 1.83. The fentalogue possessing the ratio closest to unity produced the largest enhancement subsequent to performing SABRE at earth's magnetic field. It was possible to hyperpolarize a pyridyl fentalogue selectively from a matrix that consisted largely of heroin (97 : 3 heroin:fentalogue) to validate the use of SABRE as a forensic tool. Abstract : No more hiding for pyridyl fentalogues ! The hyperpolarization technique SABRE (signal amplification by reversible exchange) is utilised for the successful enhancement of 1 H NMR signals of pyridyl functionalised fentalogues. We further demonstrate the successful selective polarization of one the fentalogues against a strong background‐signal of heroin.